Effect of sildenafil (Revatio) on postcardiac surgery acute kidney injury: a randomised, placebo-controlled clinical trial: the REVAKI-2 trial protocol. Issue 2 (18th October 2018) - Aujla, Hardeep; Kumar, Tracy; Woźniak, Marcin; Dott, William; Sullo, Nikol; Joel-David, Lathishia; Morris, Thomas; Brookes, Cassandra; Barber, Shaun; Murphy, Gavin James
Abstract : Introduction: Acute kidney injury (AKI) is a common and severe complication of cardiac surgery. The administration of pharmacological renoprotective agents during the perioperative period could prevent or reduce the severity of AKI and improve clinical outcomes. Experimental studies suggest that sildenafil may have therapeutic potential for the prevention of AKI. This trial will test the hypothesis that postoperative AKI will be reduced in cardiac surgery patients if they receive sildenafil compared with placebo. Methods and analysis: Adult cardiac surgery patients 18 years of age or above undergoing cardiac surgery with cardiopulmonary bypass and cardioplegic arrest at a single tertiary cardiac centre in the UK will be randomised in a 1:1 ratio to receive either sildenafil or placebo. The primary outcome is serum creatinine concentration measured at preoperation and daily for up to 7 days postoperatively. Secondary outcomes will include measures of inflammation, organ injury, volumes of blood transfused and resource use. Allocation concealment, internet-based randomisation stratified by operation type, and blinding of outcome assessors will reduce the risk of bias. A sample size of 112 patients will have a 90% power to detect a mean difference of 10 μmol/L for serum creatinine values between treatment and placebo control groups with an alpha value of 0.05. Ethics and dissemination: The trial protocol was approved by a UK ethics committee (reference 15/YH/0489). The trial findings will be disseminated in scientific journals and meetings. Trial registration number: ISRCTN18386427 .